Dermestes talpinus Mannerheim 1843 - Majka, Christopher G. (Zenodo, 2007)
Dermestes talpinus Mannerheim, 1843 NEW BRUNSWICK: Kent Co.: Kouchibouquac National Park, 22.vi.1978. D.B. Lyons, (2), CNC. NOVA SCOTIA: Cape Breton Co.: South Bar, 3.viii.1995, A. Brown, CBU; Colchester Co.: Shubenacadie, 19.viii.2004, D. MacDonald, NSNR; Digby Co.: Mavilette Beach, 20.vii.1993, J. & T. Cook, beach dune, JCC; Halifax Co.: Herring Cove, 5.vi.1947, D.C. Ferguson, NSMC; Kings Co.: Kentville, 11.v.1961, D.H. Webster, on decaying fox, DHWC; Kentville, 18.vii.2003, J. Ogden & N. Wood, (2), NSNR. Newly recorded in Nova Scotia. Found in the western and northern USA north to Alaska; in Canada recorded throughout the country from the Yukon and Northwest Territories and British Columbia east to New Brunswick (Beal 2003, Bousquet 1991). Found on dry carrion (Hatch 1962). In the Maritime Provinces found both on carrion and in beach drift environments. : Published as part of Majka, Christopher G., 2007, The Derodontidae, Dermestidae, Bostrichidae, and Anobiidae of the Maritime Provinces of Canada (Coleoptera: Bostrichiformia), pp. 1-38 in Zootaxa 1573 (1) on pages 9-10, DOI: 10.11646/zootaxa.1573.1.1, http://zenodo.org/record/5096635 : {"references": ["Beal, R. S., Jr. (2003) Annotated checklist of Nearctic Dermestidae with revised key to the genera. The Coleopterists Bulletin, 57 (4), 391 - 404.", "Hatch, M. H. (1962) Beetles of the Pacific Northwest, Part III. Dermestidae, pp 278 - 293. University of Washington Press, Seattle, Washington."]}